Congress House, 1995 (1995)
1995 1960-2000 "Congress House, 1995" [T0365.jpg], 1995, Trades Union Congress Congress House, London, opened in 1958, is the headquarters of the TUC. The sculptural group "The Spirit of Trade Unionism" is by Bernard Meadows.